Study guides

☆☆

Q: What is the answer to 2 plus 3A plus 9A?

Write your answer...

Submit

Related questions

It is: 12a+2 when simplified

9a^2 + 42at + 49t^2 = (3a + 7t)(3a + 7t)

a(a^2 - 9a + 3)

10a + 3a - 4a = 9a

9a + 7b *remember to look and understand the letters!*

9a+21 3(3a+7)

3a squared plus nine = 19a. 3a to the second power = 9a plus 9 = 19a.

a + 3a + 5a = 180 9a =180 a = 20

3(3a+b)

It is 3a(a+3) when factored

3a^2 + 3a^2 = 6a^2 3a^2 - 3a^2 = 0 3a^2 x 3a^2 = 9a^4 3a^2 divided by 3a^2 = 1

-3(a^2 - 3a + 7)

9a- a number is squared when it is multiplied by itself, so 3a x 3a = 9a.

In order to solve something, there needs to be an equation. If I have read your equation right you have: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) This looks like it needs to be simplified. There are two fractions being multiplied, so multiply the numerators and denominators together, giving: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) = ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) Now, simplify the polynomials to remove the squared terms and any common factors: a² - 4 = (a - 2)(a + 2) 2 + 6a = 2(1 + 3a) 3 + 9a = 3(1 + 3a) a² + 5a + 6 = (a + 3)(a + 2) Giving: ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) = ((a + 2)(a - 2)3((1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) This can now be simplified by cancelling out equivalent terms, giving: ((a + 2)(a - 2)3(1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) = ((a - 2)3) / (2(a+3)) = 3(a - 2) / 2(a + 3) = (3a - 6) / (2a + 6)

7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a

-21 = 9a - 15 - 3a -6 = 6a -1 = a

Find what you can divide both 6ax and 9a by.They can both be divided by 3, leaving 2ax and 3a.These can both be divided by a, leaving 2x and 3.So 6ax + 9a = 3a (2x + 3)The factors of 6ax + 9a are 3a and (2x + a)

(9a + 2)(9a + 2)

Are you sure it's minus 49?If so, then:9a2 +42a -49={(3a)2 + 2·3a·7 + 72} -2·72=(3a -7)2 - (7·sqrt(2))2 (2nd binomial formula)={(3a -7) + (7·sqrt(2))} · {(3a -7) - (7·sqrt(2))} (3rd binomial formula)=(3a +2,89949) · (3a -16,89949).Otherwise if it's plus 49 then simpler:9a2 +42a +49={(3a)2 + 2·3a·7 + 72}=(3a -7)2.

It is 6a + 4

-2(3a+2)+2=

a + 3a - 2 + 3a. Add the a + 3a + 3a = 7a. You can't combine the -2 & 7a so the solution is: 7a - 2.

6a-3

9a = 6a + 4 subtracting 6a from each side, 3a = 4 dividing each side by 3, a = 4/3

3a + 4b - (-6a) - 3b? There is no equivalent because you did not make it an equality. However you could combine the numbers... 3a + 4b +6a -3b = 9a + 1b